Características do acolhimento da demanda espontânea em uma unidade estratégia saúde da família em Belém do Pará: estudo quali-quantitativo - Tamargo, Roberto José Falcón (2021)
The acceptance of spontaneous demand in Primary Health Care (PHC) represents an important moment in the functioning of the work carried out by the family health teams. The development of a process of humanized, qualified and resolving all the health demands of the population that seeks primary care services represents the guarantee of the rights of users of the Unified Health System (SUS). Each health unit has specificities that must be known and evaluated to imple-ment an adequatereception process. The aim of this study is to analyzethe process of welco-ming spontaneous demand in the Tenoné 1 family health strategy unit in Belém do Pará. Me-thodology: This is a cross-sectional, observational and descriptive study, which used the quali-tative and quantitative method for data collection and analysis, which will allow us to identify how the process of welcoming the spontaneous demand of users who seek the family health strategy unit takes place, with the participation of workers. Youstudy results show thehe main characteristics of welcoming spontaneous demand in the ESF, among them are: almost half are from outside the coverage area, which could overload the work of the ESF team; regarding gender, women were the ones who most sought care; in the morning, the highest percentage of consultations took place; it was the medical professional who performed the greatest number of care and with regard to the components of care that characterized spontaneous demand, com-plaints and symptoms predominated (CDA-1), test results (CDA-4), follow-up and other reas-ons for consultation (CDA-6) and with very low expression of the diagnostic and preventive procedures component (CDA-2). Limitations and differences were identified in the perception of each worker in the meaning of welcoming, it wasThe existence of a lack of knowledge or unpreparedness is evident, with regard to the theme of welcoming health needs in the PHC units/AB, in this sense, the knowledge of the participants on this topic is empirical, guided by the dynamics of work centered on the disease and the influence of the traditional hegemonic model of medical practice. From the analysis of the results, it was verified the need to implement strategies to reorganize the reception of users and care with the involvement of the unit's workers, and thus strengthen the principles that guide the SUS.